System Formation for Assessing the Achievement of Balanced Industrial Development in the Arctic Zone - Yu. S. Bogachev; N. M. Abdikeev; P. V. Trifonov (Учёт. Анализ. Аудит, 2022)
The purpose of the study is to consider the directions of state policy in ensuring a balanced industrial growth of the Arctic zone, and to analyze the system of criteria designed to assess the level of the region development. The latter is a set of indicators — tools for managing and coordinating economic activities. They are used to comparing the results of implementing programs to build the potential of the Arctic and planned values, and should quantitatively and qualitatively reflect the results of solving the primary tasks. The authors compared the tasks in the documents defining the strategic development of the region and the existing criteria for their implementation. They proved these criteria are imperfect and do not cover the entire spectrum of economic development categories. Since it is assumed that the Arctic zone will become a driver for the development of several manufacturing industries, the authors proposed to introduce additional indicators characterizing the contribution of industry to the development of the region’s economy. The research methodology is based on the ways of empirical research, synthesis of theoretical and practical material.